THE EXISTENCE OF THE DEATH PENALTY IN THE ANTI-CORRUPTION LAW - Septiningsih , Ismawati (PT. Jurnal Center Indonesia Publisher, 2024)
The death penalty is the heaviest criminal sanction in the criminal system in Indonesia. It can be said that this is because the death penalty takes a person's life, where the right to life is the basic right of every person. In Indonesia, the death penalty is applied to general crimes with serious qualifications and special crimes which are classified as serious crimes. One specific crime that can be sentenced to death is corruption because its impact is so dangerous for the survival of a country. This article will analyze the existence of the death penalty in anti-corruption laws. The results of this research indicate that the existence of the death penalty in anti-corruption law is specifically for corruption committed under certain circumstances. The particular situation in question is corruption carried out in an emergency situation.